2017
DOI: 10.1149/2.0111711jss
|View full text |Cite
|
Sign up to set email alerts
|

Low Source/Drain Contact Resistance for AlGaN/GaN HEMTs with High Al Concentration and Si-HP [111] Substrate

Abstract: An optimized fabrication process of ohmic contacts is proposed to reduce the source/drain access resistance (R C ) and enhance DC/RF performance of AlGaN/GaN HEMTs with a high Al concentration. We show that source/drain R C can be considerably lowered by (i) optimally etching into the barrier layer using Ar + ion beam, and by (ii) forming recessed contact metallization using an optimized Ti/Al/Ni/Au (12 nm/200 nm/40 nm/100 nm) multilayers. We found that a low R C of ∼0.3 .mm can be achieved by etching closer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…These results suggest that the structure grown in this study represents a substantial enhancement in contact resistance for AlGaN/GaN heterostructures as compared to the device reported in [26][27][28]. It also reaches the value for the ohmic recess technique in [29,30], therefore demonstrating high-quality AlGaN/GaN HEMT heterostructures on silicon. The lateral leakage current and breakdown voltage of the heterostructures grown on Si with and without BB were evaluated using a TLM structure with a spacing of 10 µm, as shown in figure 6(a).…”
Section: Resultssupporting
confidence: 61%
“…These results suggest that the structure grown in this study represents a substantial enhancement in contact resistance for AlGaN/GaN heterostructures as compared to the device reported in [26][27][28]. It also reaches the value for the ohmic recess technique in [29,30], therefore demonstrating high-quality AlGaN/GaN HEMT heterostructures on silicon. The lateral leakage current and breakdown voltage of the heterostructures grown on Si with and without BB were evaluated using a TLM structure with a spacing of 10 µm, as shown in figure 6(a).…”
Section: Resultssupporting
confidence: 61%
“…The contact resistance measurement was determined using TLM patterns with spacings (𝑑) of 12, 14, 18, and 26 μm, and the width (𝑊) was 100 μm. Measurements of total resistance (𝑅 𝑇 ) across each contact pair were measured to construct the TLM graph [34] using a four-point probe arrangement, as shown in Figure 4. The measured 𝑅 𝑇 can be expressed by Equation (1) as follows:…”
Section: Contact Resistance Evaluation With Tlm Measurementmentioning
confidence: 99%
“…To date, the exploration of etching patterns to minimize ohmic contact resistance has pursued several directions, including the analysis of various pattern morphologies and arrangements [19,[23][24][25], pattern dimensions [22,24,25,32], and etching depths [22][23][24]. Among the diverse etching pattern morphologies paired with different arrangements, commonly utilized ones are symmetrically arranged holes [19,[22][23][24]32,34], closely packed holes [38], and lines in the direction of current flow [19,25]. Additionally, some groups have crafted grid-like patterns composed of horizontal and vertical lines [23] and patterns where the holes gradually increase in size from small to large [24], in which You et al investigated the effects of various hole array arrangements on ohmic contact, confirming that devices with gradually increasing hole patterns of 1/3/5 μm demonstrated lower contact resistance compared to those with uniformly sized patterns.…”
Section: Characteristics Of Algan/gan Hemts Utilizing Sub-10 Nm Nanoh...mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In recent years, the application of GaN to silicon substrate has become increasingly widespread due to its low cost, larger size, acceptable thermal conductivity, and ease of integration with complementary-metal-oxide semiconductor circuits. 5,6 The challenges of GaN-on-silicon high-electron-mobility transistors (HEMTs) include lossy substrates and large thermal expansion coefficient mismatches between GaN and Si substrates. 7 Several studies have reported the backgrind and backside metallization of HEMT on silicon substrate for compact packages and efficient heat dissipation.…”
mentioning
confidence: 99%